An improved Q estimation approach: the weighted centroid frequency shift method. (23rd May 2016) - Li, Jingnan; Wang, Shangxu; Yang, Dengfeng; Dong, Chunhui; Tao, Yonghui; Zhou, Yatao
Abstract: Seismic wave propagation in subsurface media suffers from absorption, which can be quantified by the quality factor Q . Accurate estimation of the Q factor is of great importance for the resolution enhancement of seismic data, precise imaging and interpretation, and reservoir prediction and characterization. The centroid frequency shift method (CFS) is currently one of the most commonly used Q estimation methods. However, for seismic data that contain noise, the accuracy and stability of Q extracted using CFS depend on the choice of frequency band. In order to reduce the influence of frequency band choices and obtain Q with greater precision and robustness, we present an improved CFS Q measurement approach—the weighted CFS method (WCFS), which incorporates a Gaussian weighting coefficient into the calculation procedure of the conventional CFS. The basic idea is to enhance the proportion of advantageous frequencies in the amplitude spectrum and reduce the weight of disadvantageous frequencies. In this novel method, we first construct a Gauss function using the centroid frequency and variance of the reference wavelet. Then we employ it as the weighting coefficient for the amplitude spectrum of the original signal. Finally, the conventional CFS is adopted for the weighted amplitude spectrum to extract the Q factor. Numerical tests of noise-free synthetic data demonstrate that the WCFS is feasible and efficient, and produces more accurate results than the conventional CFS. Tests for noisy synthetic data indicate that the new method has better anti-noise capability than the CFS. The application to field vertical seismic profile (VSP) data further demonstrates its validity05 .